UDC 621.565.93/95 PREVENTION OF EXTERNAL FLOOD FORMATION ON THE SURFACE OF HEAT EXCHANGER PIPES: Maqola - Adashev, Bexzod; Ismailov, Mirzaakbar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Purpose of the work. There are various methods for preventing scale formation on heating surfaces and cleaning surfaces from scale: chemical, mechanical, and methods related to the management of hydrodynamic modes. Since these methods require certain costs and time, their use in the processes of thermal treatment of food products is not always effective. For this reason, the transfer of water used as a coolant in heat exchange devices to the heating process by means of a magnetic field is one of the modern methods that allows reducing the slag layer. The scale layer is usually removed by acid washing of the internal heat exchange surfaces or mechanical washing. However, both methods involve the use of a substantial amount of chemicals and result in highly polluted wastewater. In addition, it significantly increases operating costs. The article uses statistical methods for processing experimental data, and generally accepted methods for conducting experiments to study the patterns of scale formation using control and measuring instruments and accurate methods for measuring technological parameters. The main purpose of the paper is to study the influence of a constant magnetic field on the formation of mineral salts deposits on the surface of walls of thermal appliances used in chemical, oil refining, and food processing industry